FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN SUB SEKTOR PERTANIAN DI KABUPATEN TANAH BUMBU - AYU PERTIWI (PPJP Universitas Lambung Mangkurat, 2018)
The purposes of this research are (1) To understand the effect of production, land area and human resources to the development of agriculture sub-sector in Tanah Bumbu District; (2) Which sub-sector is the most important to the development of agriculture sub-sector in Tanah Bumbu District. The object of this research are three sub-sectors in Tanah Bumbu District (agriculture, forestry and fishery). The method of this research is regression analysis of panel data with the Common Effect model. The result of this research that production, land area and human resources both individually (partial) and together give positive effect and significant to the development of agriculture sub-sector in Tanah Bumbu District. Forestrey sub-sector which gives the most positive contribution to the development of the agriculture sub-sector in Tanah Bumbu District. Keywords : Production, Land Area, Human Resources, The Development of Agriculture Sub-sector